Work without stress building a resilient mindset for lasting success - Roger, Derek 1946-; Petrie, Nick (McGraw Hill-Ascent Audio, 2016)
If you're like most people, you probably think that stress is an inevitable part of life. The truth is: it's not. In a groundbreaking 30-year study, Dr. Derek Roger has discovered that everything we think we know about stress-and how we should "manage" it-is just plain wrong. STRESS IS A CHOICE. It is not a natural response to the pressures of work. It's a choice that you make, consciously or not, to worry and fret and agonize over the work you need to do-instead of just doing it. WORK DOESN'T HAVE TO BE STRESSFUL FOR YOU TO BE SUCCESSFUL. This book offers a radically different approach to stress. It's about being resilient. Flexible. Mentally awake and in the moment. It's about changing your mindset to keep things in perspective instead of adding fuel to the fire with negative thoughts. The techniques you'll find in this book are powerful, practical, and proven to work-without stress. A revolutionary approach to preventing stress that is evidence-based, life-changing, and scientifically proven to work Why do some people get stressed while others stay calm, cool, and collected under pressure? According to renowned stress researcher Dr. Derek Roger, the answer lies in resilience-your ability to cope with challenges and thrive under adversity-rather than ruminating and obsessing over them. In lab-controlled studies, he discovered that the key to "managing" stress is to stop it before it starts. To be resilient, flexible, and ready for anything. The culmination of three decades of research, this book presents a practical and proven program of simple step-by-step techniques that you can use to: * Adjust your mindset and work more efficiently * Control your response to any kind of pressure * Detach and let go of negative thoughts * Put things in perspective and focus on what matters * Develop a stress-free leadership style * Build more resilient teams and organizations * Give constructive feedback and communicate effectively * Differentiate between caring (useful) and worrying (useless) * Open your mind to new approaches and ideas * Reach higher levels of success-without all the stress Warning: This is not another stress management book. It's not about finding time to relax. It's about cultivating resilience-the ability to negotiate the rapids of life without being swept away. It's about reprogramming your emotional responses to high-pressure situations and breaking the self-defeating habits that do nothing but increase your levels of stress. In this book, you'll find case-by-case studies and day-to-day techniques to help you readjust your attitude from the moment you wake up. You'll discover essential tools for a stress-free life, including 3 questions to ask in a crisis, 4 steps to handle everyday pressures, and 8 behaviors that alleviate stress instantly. Best of all, the book shows you how to instill a no-stress approach to work in your fellow employees, throughout your organization. Remember: You are not genetically programmed to experience stress. You have a choice. You can make your success the hard way-or you can Work Without Stress.
Online resource; title from title details screen (O'Reilly, viewed September 27, 2022)
Keywords: Job stress; Stress (Psychology); Resilience (Personality trait); Stress; Résilience (Trait de personnalité); Downloadable audio books; Audiobooks; Livres audio